Attitude of Male Inservice and Preservice Earlychildhood Teachers towards Working in Preschool Centers in Ibadan, Nigeria - Moses Amosun; Lawrence Ogunniyi; Funke Ogunbiyi (Faculty of Teacher Training and Education, Universitas Terbuka, 2021)
Preschool Education provides foundation for all round development, enables the child to understand various issues and fit in well into the society. Although it is the duty of both male and female early childhood educators to help children develop holistically, statistics has shown that more female care givers work in preschool centers across the country than male. Even in some foreign countries, this problem remains the same. However, researches have tried to identify the cause of this gender inequality or disparity but have only sampled the opinion of others about this without adequately considering the attitude of the male early childhood educators. Hence, this study investigated the attitude of male early childhood educators towards working in preschool centers in Ibadan. The study adopted a mixed method research approach and the design is explanatory triangulation of QUAN + QUAL type. Proportional stratified sampling technique was used to select 150 in-service and 150 pre-service male early childhood educators from the 3 local government areas selected. One instrument was used to gather the quantitative data. Interview of in-services and pre-service early childhood educators also form source of qualitative data. The study found out that the attitude of early childhood educators is not encouraging. It also found out that there is no significant difference between in-services and pre service early childhood educators in their attitude towards working in preschool. It was recommended that investment should be made into early childhood education level so as to make the salary attractive for most male educators.